Dualisme Peran BAZNAS dalam Pengelolaan Zakat di Indonesia - Joni Apriansah (CV. Ulil Albab Corp, 2026)
One of the reasons why the realization of ZIS receipts in Indonesia has always been smaller than its potential is the result of weaknesses in its governance. More specifically, one of the weaknesses in the governance of ZIS in Indonesia so far is the dualism of the role of BAZNAS which creates a dualism of trust and no focus on management. This paper intends to find out the description of ZIS governance in Indonesia, the role of BAZNAS in ZIS governance, and the implications of the dualism of BAZNAS' role in ZIS governance in Indonesia. The method used in this paper is qualitative with a document study approach. This paper finds that: 1) Management of zakat and/or ZIS is carried out by BAZNAS nationally. BAZNAS in the implementation of zakat collection and distribution is assisted by UPZ and LAZ. ZIS management is carried out with four main systems namely planning, implementation, control, and reporting. 2) The role of BAZNAS in the governance of ZIS in Indonesia is as a management agency authorized to carry out management tasks nationally. 3) BAZNAS as the operator is tasked with receiving ZIS from muzakki/donors and distributing it to mustahik, while as coordinator BAZNAS coordinates zakat management with all zakat management organizations in Indonesia. The positive implication of this dualism is the strengthening of institutions, human resources, governance, and networks. The negative implications of dualism of roles lie in the suboptimal pattern of coordination, low understanding of fiqh and zakat regulations, and low competence of human resources. If the role as operator and coordinator is removed, then BAZNAS can apply several models such as the ANP, ZCP, and decentralized zakat corporatization models.